2016
DOI: 10.21109/kesmas.v11i1.687
|View full text |Cite
|
Sign up to set email alerts
|

Rural-Based Health Promotion Model for Pregnant Women in Banyumas District

Abstract: Previous studies show that knowledge of prenatal care in rural areas remains low affecting on bad behavior, so developing health promotion models is needed to improve prenatal care knowledge, attitude and behavior. This study aimed to develop health promotion model of prenatal care in rural area based on needs assessment. Study was conducted on June 2015 by qualitative approach involving first 16 pregnant women in third trimester with risky pregnancy as key informants and 16 family members living with them and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Previous research suggested the importance of health promotion media in the form of books for pregnant women with attractive designs featuring pictures, colors and full explanations. The book was chosen because of the trends and needs of pregnant women, the characteristics of the region and the availability of infrastructure (Gamelia et al, 2016). Based on these results, Public Health Center officers are expected to improve their ability to use the media and, if possible, gradually develop a media suitable with their clients' characteristics.…”
Section: Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggested the importance of health promotion media in the form of books for pregnant women with attractive designs featuring pictures, colors and full explanations. The book was chosen because of the trends and needs of pregnant women, the characteristics of the region and the availability of infrastructure (Gamelia et al, 2016). Based on these results, Public Health Center officers are expected to improve their ability to use the media and, if possible, gradually develop a media suitable with their clients' characteristics.…”
Section: Informationmentioning
confidence: 99%
“…Operational innovations in the field are emerging but sometimes, the information is unknown to the Public Health Center officers. Some were revealed through research such as the development of health promotion models for rural-based pregnant women in Banyumas (Gamelia et al, 2016). In addition, there is the effect of multilevel intervention in the promotion of occupational health against metabolic syndrome components among workers (Zahtamal & Chandra, 2011).…”
Section: Informationmentioning
confidence: 99%
“…Researchers found different conditions to the results of research Gamelia et al [12] have examined the determinants of behavioral treatments Pregnancy and found that this type of work, income, parity, knowledge, attitudes and the role of the midwife has no influence on pregnancy care.…”
Section: Anggo Dompak Denggan Sibuk Paresoon Ma Tu Bidan Harana Anggmentioning
confidence: 99%